2018
DOI: 10.1080/19491034.2018.1498707
|View full text |Cite
|
Sign up to set email alerts
|

KDM2A/B lysine demethylases and their alternative isoforms in development and disease

Abstract: Aberrant levels of histone modifications lead to chromatin malfunctioning and consequently to various developmental defects and human diseases. Therefore, the proteins bearing the ability to modify histones have been extensively studied and the molecular mechanisms of their action are now fairly well understood. However, little attention has been paid to naturally occurring alternative isoforms of chromatin modifying proteins and to their biological roles. In this review, we focus on mammalian KDM2A and KDM2B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 140 publications
(243 reference statements)
1
32
0
2
Order By: Relevance
“…Therefore, KDM2A/B-SF are not able to demethylate the KDM2A/B target lysines, but they still have the ability to bind to the same DNA regions as KDM2A/B-LF and to interact with the same proteins as KDM2A/B-LF. KDM2A/B-SF are thus likely to compete with KDM2A/B-LF or to complement their function (1). Despite the fact that a KDM2A-SF specific knockout mutant has not been described yet and it cannot be compared to the embryonically lethal KDM2A-LF knockout phenotype (24), we previously showed that the distinct KDM2A positive nuclear structures on pericentromeric heterochromatin are formed by KDM2A-SF and not by KDM2A-LF (12).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, KDM2A/B-SF are not able to demethylate the KDM2A/B target lysines, but they still have the ability to bind to the same DNA regions as KDM2A/B-LF and to interact with the same proteins as KDM2A/B-LF. KDM2A/B-SF are thus likely to compete with KDM2A/B-LF or to complement their function (1). Despite the fact that a KDM2A-SF specific knockout mutant has not been described yet and it cannot be compared to the embryonically lethal KDM2A-LF knockout phenotype (24), we previously showed that the distinct KDM2A positive nuclear structures on pericentromeric heterochromatin are formed by KDM2A-SF and not by KDM2A-LF (12).…”
Section: Introductionmentioning
confidence: 97%
“…KDM2B is able to demethylate also H3K4me3 (3). By demethylating H3K36me1/2 and H3K4me3 in transcriptionally active promoters (4)(5)(6), KDM2A/B function as transcriptional repressors of the promoters that contain CpG islands (1,(7)(8)(9)(10). Although KDM2A and KDM2B have very similar 3 structure, they have been shown to interact with different protein partners to repress different target regions.…”
Section: Introductionmentioning
confidence: 99%
“…KDM2A and KDM2B (KDM2A/B) are two closely related lysine demethylases with the ability to bind to non-methylated CpG islands through their CXXC DNA binding domain. After binding to non-methylated CpG islands in transcriptionally active promoters, KDM2A/B demethylate mono- and di-methylated H3K36 lysines (H3K36me1/2) using their N-terminal Jumonji-C demethylase domain [ 1 , 2 ]. KDM2B is able to demethylate also H3K4me3 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…KDM2B is able to demethylate also H3K4me3 [ 3 ]. By demethylating H3K36me1/2 and H3K4me3 in transcriptionally active promoters [ 4 6 ], KDM2A/B function as transcriptional repressors of the promoters that contain CpG islands [ 1 , 7 10 ]. Although KDM2A and KDM2B have very similar structure, they have been shown to interact with different protein partners to repress different target regions.…”
Section: Introductionmentioning
confidence: 99%
“…Los modificadores de cromatina más importantes que median esta trimetilación pertenecen a la familia MLL y a los complejos SETD1 y 2 (40,270), mientras que son varias las demetilasas (KDMs) que se encargan de la eliminación del grupo metilo de este residuo. Una de ellas es KDM2B, capaz de demetilar esta lisina de la histona H3 junto con otras dos marcas epigenéticas (H3K36me1/2 y H3K79me2/3) en los promotores transcripcionalmente activos (271). Las demás pertenecen a la subfamila KDM5 y se caracterizan por la presencia de un dominio catalítico JmjC y por demetilar también a la H3K4me2 (272).…”
Section: Regulación De La Trimetilación De La Lisina 4 De La Histonaunclassified